Diagnostic and clinical implications of anorectal lymphogranuloma venereum in men who have sex with men: a retrospective case-control study - Van der Bij, Akke K; Spaargaren, Joke; Morré, Servaas A; Fennema, Han S A; Mindel, Adrian; Coutinho, Roel A; de Vries, Henry J C (Clinical infectious diseases, 2006)
Recently, outbreaks of anorectal lymphogranuloma venereum (LGV) have occurred among men who have sex with men (MSM). This study identifies risk factors and clinical predictors of LGV to determine the implications for clinical practice. The Chlamydia trachomatis serovars for all MSM who had anorectal chlamydia diagnosed at a sexually transmitted infection clinic in Amsterdam, The Netherlands, in 2002 and 2003 were retrospectively typed; 87 persons were infected with C. trachomatis serovar L2b and received a diagnosis of LGV. MSM infected with C. trachomatis serovars A-K and who thus had non-LGV anorectal chlamydia (n = 377) and MSM who reported having receptive anorectal intercourse but who did not have anorectal chlamydia (n = 2677) served as 2 separate control groups. Risk factors and clinical predictors were analyzed by multivariate logistic regression. Receiver operating characteristic curves were used to determine clinical relevance. HIV seropositivity was the strongest risk factor for LGV (odds ratio for patients with LGV vs. those with non-LGV chlamydia, 5.7 [95% confidence interval, 2.6-12.8]; odds ratio for patients with LGV vs. control subjects without chlamydia, 9.3 [95% confidence interval, 4.4-20.0]). Proctoscopic findings and elevated white blood cell counts in anorectal smear specimens were the only clinically relevant predictors for LGV infection (area under the curve of the receiver operating characteristic curve, > 0.71). Use of these 2 parameters and HIV infection status provided the highest diagnostic accuracy (for MSM with anorectal chlamydia, the area under the curve was > 0.82; sensitivity and specificity were 89% and 50%, respectively). LGV testing is recommended for MSM with anorectal chlamydia. If routine LGV serovar typing is unavailable, we propose administration of syndromic LGV treatment for MSM with anorectal chlamydia and either proctitis detected by proctoscopic examination, > 10 white blood cells/high-power field detected on an anorectal smear specimen, or HIV seropositivity.